1991
DOI: 10.1002/hlca.19910740842
|View full text |Cite
|
Sign up to set email alerts
|

Convenient Synthesis of 2‐Azido‐2‐deoxy‐aldoses by Diazo Transfer

Abstract: Dedicated to Prof. Dr. Anronio G6mez-Sbnchez on the occasion of his 65th birthday.(5.1X.9 1) Diazo transfer from trifluoromethanesulfonyl azide (TfN,) to 2-amino-2-deoxy-glycoses constitutes a high-yielding, simple procedure for the preparation of partially protected or unprotected 2-azido-2-deoxy-aldoses. Thus, the o-allosamine derivative 2 gave 93% of 3, while diazo transfer to o-glucosamine, o-mannosamine, and o-galactosamine, followed by acetylation, yielded the azides 5, 7, and 9 in yields of 74-91, 65, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
105
0
1

Year Published

1999
1999
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 160 publications
(109 citation statements)
references
References 18 publications
3
105
0
1
Order By: Relevance
“…Previous experience has shown that the trichloroacetimidate method [26] using 2-azido-2-deoxy-glucose as glycosyl donor is the method of choice for glycosylating the poorly reactive hydroxyl groups of cyclitols in general, and the axially oriented hydroxyl groups in particular. The two glycosyl donors 9 and 10 were obtained from the readily available 1,3,4,6-tetra-O-acetyl-2-azido-2-deoxy--glucose [27] as previously reported. [7] Condensation of trichloroacetimidate 9 with 8 in dichloromethane at room temperature using TMSOTf as a promoter gave the desired disaccharide 11 in 75% yield as an α/β mixture (1.4:1) (Scheme 2).…”
Section: Resultsmentioning
confidence: 99%
“…Previous experience has shown that the trichloroacetimidate method [26] using 2-azido-2-deoxy-glucose as glycosyl donor is the method of choice for glycosylating the poorly reactive hydroxyl groups of cyclitols in general, and the axially oriented hydroxyl groups in particular. The two glycosyl donors 9 and 10 were obtained from the readily available 1,3,4,6-tetra-O-acetyl-2-azido-2-deoxy--glucose [27] as previously reported. [7] Condensation of trichloroacetimidate 9 with 8 in dichloromethane at room temperature using TMSOTf as a promoter gave the desired disaccharide 11 in 75% yield as an α/β mixture (1.4:1) (Scheme 2).…”
Section: Resultsmentioning
confidence: 99%
“…The effects of 3 have been studied on stage 18 otic vesicles that were isolated and cultured for 24 h. A typical experiment is shown in Figure 1 top in which the effect of 3 at concentrations of 1 and 10 mm is compared with otic vesicles grown in parallel without additions (0S) or in the presence of 1 nm insulin-like growth factor I (IGF-I). Otic vesicles incubated with 3 acquired a morphology that corresponded to stage 19 otic vesicles developed in vivo. The rate of DNA synthesis was estimated in parallel experiments by measuring Compound 3 also modulates Fos levels in the otic vesicle, and Figure 2 shows a Western blot analysis of otic vesicles stimulated with 3 at different times.…”
Section: Biological Activitymentioning
confidence: 97%
“…[17] These glycosyl donors were prepared as indicated in Scheme 1. The acetylated donor 8 [18] was synthesized from the readily available derivative 6 [19] by selective removal of the 1-O-acetyl group [20] and trichloroacetimidate formation under established conditions. [16] The benzylated donor 12 [21] was prepared Abstract in Spanish: Se describe una estrategia sintØtica para la preparacio Ân de una serie de compuestos relacionados con los inositol fosfoglicanos propuestos como segundos mensajeros (compuestos 3-5) y sus correspondientes precursores (glicosil fosfatidilinositoles de tipo 1 y 2).…”
Section: Synthesismentioning
confidence: 99%
“…The flash cromatographic purification over silica gel [α] D +36.7 (c 1.6, CHCl 3 ) for a 2:3 mixture of α-and β-anomers; NMR data were in full accordance with those reported. 24 …”
Section: -Methoxyphenyl 2-azido-2-deoxy-346-tri-o-acetyl-β-d-galacmentioning
confidence: 99%